Clinical profile of acute appendicitis at the National Referral Hospital in Bhutan - Chopel, Thukten; Tshering, Sangay; Dorji, Namkha; Dorji, Thinley; Dorjee, Sithar; Tenzin, Tashi (Journal of Society of Surgeons of Nepal, 2022)
Introduction: Acute appendicitis poses a diagnostic challenge in a low-resource setting like ours. Without timely and appropriate management, acute appendicitis can lead to prolonged morbidity and mortality. We describe the clinical profile of acute appendicitis at the national referral hospital in Bhutan. Method: This was a cross-sectional descriptive study of all cases of acute appendicitis managed at the National Referral Hospital, Bhutan from 1st January-31st December 2016. Data related to patients’ symptoms, clinical examination and ultrasonographic findings, treatment details, length of hospital stay, and histopathology report were analyzed. Results: Of the 3291 surgical admissions, there were 173 patients with acute appendicitis contributing to 5.3% of the total surgical burden. The median age was 27 years (IQR 20, 39), 60.1% were males. 96.5% and 91.9% of the patients presented with right iliac fossa pain and tenderness respectively. While 74.6%(n=129) had primary surgery, 18.9%(n=32) were managed conservatively. Of the 32 patients, 37.5%(n=12) had surgery after failed conservative management. Seventy-five percent presented with intraoperative features of complicated appendicitis. The negative appendectomy rate was 2.2%. The median length of hospital stay was three days (range 3–60). Ultrasonographic diagnosis compared to histopathological confirmation had a sensitivity of 87.8%, kappa agreement of 87.3%, and specificity of 66.7%. Conclusion: Acute appendicitis is a common surgical emergency. Ultrasonography in the diagnosis of acute appendicitis was useful in a low-resource setting. A high proportion of complicated acute appendicitis in our setting needs effective interventional strategies.